The roles and actions of sex traffickers in Cyprus: an overview - Constantinou, Angelo G. (Trends in organized crime, 2020)
While the preponderance of delineation, exploration, and analysis of human trafficking concentrates on the victimization of trafficked people, the offenders’ criminal partaking is often left unexplored. That said, this study aims to examine the conundrum of human trafficking by exploring the traffickers’ demographics, tactics, connections, and collaborations. In order to accomplish this, data are drawn from the content analysis of 102 police interviews (Cyprus Police) with victims of trafficking and the study of police files of 18 persons convicted for human trafficking and sexual exploitation. In short (and contrary to widely held beliefs), the findings point out that human trafficking in Cyprus is not premised on well-established criminal syndicates with deep roots and solid networking, nor is dominated by cruel tactics actuated by meticulous crooks, linked to corrupt officials.